ANTI-JCV TITRES INCREASE OVER TIME WITH NATALIZUMAB TREATMENT. Issue 11 (14th October 2015) - Raffel, Joel; Gafson, Arie; Nicholas, Richard
Abstract : Objectives: This study sought to evaluate rates of anti-JCV antibody seroconversion and prospective change in antibody titre in a cohort of people with MS receiving natalizumab. Methods: Anti-JCV antibody results (n=1154) from the second-generation STRATIFY JCV™ DxSelect™ test were analysed from an observational cohort of MS patients on natalizumab (n=485; n= 340 with repeat testing). Results: At baseline, 59% (287/485) of patients were JCV seropositive; 33% (162/485) had a high anti-JCV antibody index (> 1.5). Baseline titres and rates of seropositivity increased slightly with baseline patient age. With multiple tests repeated over time, 22.3% of seronegative patients converted to seropositive. When comparing pairs of prospective tests, seroconversion rate was greater than seroreversion rate (40/373 (10.7%) vs 18/296 (6.1%); p<0.05). Moreover, anti-JCV antibody titres increased across prospective paired tests (mA-B 0.095; paired t(668)=4.6; p<0.0001) – an effect that was independent of baseline sample titre. This magnitude of antibody level increase far exceeds that expected due to age alone. Conclusions: Our data suggest that natalizumab therapy itself causes anti-JCV antibody titres to increase over time. Future work should investigate the underlying mechanisms, and clinical relevance to risk stratification of this phenomenon.